2014
DOI: 10.1055/s-0034-1393935
|View full text |Cite
|
Sign up to set email alerts
|

A Clinical Scoring System to Predict the Development of Bronchopulmonary Dysplasia

Abstract: With this easy to use scoring system, one can predict the neonate at risk for BPD at 72 hours of life and direct preventive measures toward these infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Despite these efforts, no reliable and reproducible risk stratification model has been found that would allow an early diagnosis and ease of application within NICUs. A single predictive factor cannot accurately predict the BPD outcome because BPD is a multifactorial disease, and therefore current multivariate modeling demonstrates that the greater the number of clinical predictor variables, the better the modeling results tend to be (Laughon et al, 2011;Gursoy et al, 2015). However, this also increases complexity and impairs practicality in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite these efforts, no reliable and reproducible risk stratification model has been found that would allow an early diagnosis and ease of application within NICUs. A single predictive factor cannot accurately predict the BPD outcome because BPD is a multifactorial disease, and therefore current multivariate modeling demonstrates that the greater the number of clinical predictor variables, the better the modeling results tend to be (Laughon et al, 2011;Gursoy et al, 2015). However, this also increases complexity and impairs practicality in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…(AUROC) ranged from 0.50 to 0.76 for BPD in an external validation study of a systematic review (Onland et al, 2013). Additionally, the ratio of tidal expiratory flow at 50% of expired volume to peak tidal expiratory flow (as one of the mechanical ventilation parameters) gave an AUROC for the development of moderate/severe BPD (sBPD) of 0.774 (Bentsen et al, 2018); mechanical ventilation at 1 week provided an AUROC for the development of BPD and sBPD of 0.77 and 0.83 (Hunt et al, 2018), respectively; and a multifactorial model that included BW, GA, sex, presence of a hemodynamically significant patent ductus arteriosus (as diagnosed by an echocardiogram), respiratory distress syndrome, hypotension within the first 72 h of life, and intraventricular hemorrhage (IVH) delivered an AUROC for the development of BPD of 0.930-which showed a noticeably improved discriminatory performance, but without favorable clinical maneuverability (Gursoy et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, no single biomarker or combination of biomarkers with a good predictive value has been found. A great number of predictive models using clinical variables have been developed, but none has been able to determine which high-risk patients will eventually develop BPD [13, 14, 24]. Most predictive models agree on a number of BPD risk factors, such as birth weight, GA, chorioamnionitis, preeclampsia, respiratory parameters, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers came to the same conclusion (16). Respiratory distress syndrome (RDS) is a common cause of morbidity and mortality related to premature birth and most infants who develop BPD initially suffer from acute RDS (17). Infants with RDS may easily have acidosis due to adverse pulmonary ventilation.…”
Section: Postnatal Characteristicsmentioning
confidence: 99%